Physicians' attitudes on the implementation of an antimicrobial stewardship program in Lebanese hospitals - Nathalie Sayegh; Souheil Hallit; Rabih Hallit; Nadine Saleh; Rouba K. Zeidan (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Background: Misuse of antibiotics and antimicrobial resistance are global concerns. Antibiotic stewardship programs (ASP) are advocated to reduce pathogens resistance by ensuring appropriate antimicrobial use. Several factors affect the implementation of ASPs in hospitals. The size and types of care provided, as well as the complexity of antibiotic prescription, are all issues that are considered in designing an effective hospital-based program. Objectives: To examine physicians' attitude on implementation of an antimicrobial stewardship program in Lebanese hospitals. Methods: A descriptive cross-sectional survey was carried out using an online questionnaire. Survey items assessed ASP implementations, physicians' attitudes, usefulness of the tools, and barriers of implementation. The questionnaire was based on the Center for Disease Control core-elements. Results: 158 physicians completed the survey with a response rate of 4%. Our results showed that the majority (66%) of physicians were familiar with the ASP concept. Most respondents reported a lack of regular educational programs (41%), as well as a lack of support from the medical staff (76%). This study demonstrated positive attitudes and support for ASP implementation. However, ASPs were reported as affecting physicians' autonomy by 34 % of the participants. Antibiotic rounds and prospective audit and feedback were rated as most useful interaction methods with the ASPs. A minimal support of the Ministry Of Public Health, as well as the absence of regulation and of national guidelines, were reported as barriers to ASPs. The shortage of Infectious Disease physicians was seen as a barrier by half of the respondents. Conclusions: Physicians are supportive of ASP, with preference for interventions that provide information and education rather than restrictive ones. Additional research is needed on a larger sample of physicians.